Avaliação nutricional e conformidade da rotulagem de “petiscos” consumidos por crianças à legislação brasileira - Garcia, Márcia Regina; Vieites, Rogério Lopes [UNESP]; Daiuto, Erica (EIA Energy in Agriculture, 2015)
Label is every and any information regarding to a product that is transcribed in its package. For the consumer it is through the nutritional information tables contained in the labels that there is access to data such as quantity and percentage of nutrients contained in foods. Through this knowledge, it is possible to make healthier food choices, minimizing the negative effects related to poor nutrition in the population, especially among children, the most critical rate of obesity incidence. The aim of this study was to evaluate the appropriateness of the labels of some foods consumed by children in relation to the Recommended Daily Intake (RDI) and verify that the general aspects of the labels were in accordance with Brazilian regulations. Five products were selected like snacks, corn snacks, snacks, peanut, peanuts, potato snacks and biscuit recipes. The labels of different brands of each snack were analyzed using the Checklist of Labelling, which is based on RDC No. 259 and RDC No. 360. The nutritional adequacy of nutrients from these foods (carbohydrates, protein, total fat, saturated fat, trans fat, dietary fiber and sodium) was evaluated in relation to that recommended by the RDA for children 4-8 years old. There was small percentage of mistakes in the labels of the analyzed foods, about 12%, being the presence of words that induce the consumers to the misunderstanding the irregularity with larger predominance, present in 25% of the labels. Other items in disagreement were the incomplete specification of the addictive ones alimentary in the list of ingredients and the absence of instructions about the conservation of the foods after opening the packings, both with percentile of occurrence of 18,75%. The high sodium content found in the nutritional information of food shows that should reduce the consumption of these products among children.

Rótulo é toda e qualquer informação referente a um produto que esteja transcrita em sua embalagem. Para o consumidor é por meio das tabelas de informação nutricional contidas nos rótulos que se tem acesso a dados como quantidade e porcentagem dos nutrientes presentes nos alimentos. Através desse conhecimento, pode-se realizar escolhas alimentares mais saudáveis, mitigando os efeitos negativos referentes à má nutrição na população, principalmente entre as crianças, alvo mais crítico da incidência da obesidade. O objetivo desta pesquisa foi avaliar a adequação dos rótulos de alguns alimentos consumidos pelo público infantil, em relação à Ingestão Diária Recomendada (IDR) e verificar se os aspectos gerais dos mesmos estavam em acordo com a legislação brasileira vigente. Para esse estudo foram selecionados cinco produtos embalados, tipo petiscos: salgadinho de milho, salgadinho de amendoim, amendoim, snacks de batata e biscoito de polvilho. Os rótulos de diferentes marcas de cada petisco foram analisados por meio da Ficha de Avaliação de Rotulagem, elaborada com base nas RDC N° 259, de 20 de setembro de 2002 e RDC N° 360, de 23 de dezembro de 2003. A adequação nutricional dos nutrientes destes alimentos (carboidratos, proteínas, gordura total, gordura saturada, gordura trans, fibra alimentar e sódio) foi avaliada em relação à preconizada pela IDR para crianças de 4 a 8 anos de idade. Houve pequena porcentagem de erros nos rótulos dos alimentos analisados, cerca de 12%, sendo a presença de vocábulos que induzem os consumidores ao equívoco a irregularidade com maior predominância, presente em 25% dos rótulos. Outros itens em desacordo foram a incompleta especificação dos aditivos alimentares na lista de ingredientes e a ausência de instruções sobre a conservação dos alimentos após abertura das embalagens, ambos com percentual de ocorrência de 18,75%. O alto teor de sódio verificado na informação nutricional dos alimentos demonstra que deve-se mitigar o consumo destes produtos entre a população infantil.
Nutritional evaluation and compliance labelling of "snacks" consumed by children to the brazilian regulations
Keywords: Childhood obesity; Labels; Nutritional adequacy; Obesidade infantil; Rótulos; Adequação nutricional